The Relationship between Students’ Learning Motivation and Learning Outcomes through Guided Discovery Model Assisted Video and Interactive Simulation (Jurnal Pendidikan Fisika, 2021)
This study aims to (1) implement the Guided Discovery Learning Model Assisted Video and Interactive Simulation (GDM-VIS) in physics learning on the concept of statistical fluids; (2) identify the relationship between students’ motivation and learning outcomes. This research is a pre-experimental research employing One Shoot Case Study design. The learning model and instruments that have been developed were used in a class of 38 students before the distance learning was applied. The data of learning motivation were obtained through motivation questionnaire, while learning outcome data were obtained by means of a conceptual understanding test instrument. To see whether there is a correlation between students’ motivation and learning outcomes, the Bivariate Pearson analysis with SPSS was used. Based on the results of the analysis, the value obtained based on the value or relationship (R) was 0.613. Furthermore, the coefficient of determination (R Square) was 0.375, meaning that the effect of learning motivation with the application of GDM-VIS toward concept understanding is 37.5%. Based on the Output Coefficients, decision making in a simple regression test, and based on the significance value of the Coefficients table, it was obtained that the significance value was 0.00
Keywords: GDM-VIS; Learning Motivation; Understanding Concepts